2019
DOI: 10.1186/s13071-019-3461-4
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus detection, isolation and genome sequencing through Culicidae sampling during the epidemic in Vitória, Espírito Santo, Brazil

Abstract: Background Zika virus (ZIKV) has been isolated from many mosquito species in nature, but it is believed that the main vectors in urban environments are species of the genus Aedes . Here, we detected and isolated ZIKV in samples from Aedes aegypti , Aedes taeniorhynchus and Culex quinquefasciatus , collected during the Zika epidemic in Vitória, southeast Brazil. Using quantitative real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…aegypti, (28) although Culex quinquefasciatus females have been collected naturally infected with ZIKV. (29) Besides that, the presence of Ae. albopictus in Brazil was first recorded in 1986 in Rio de Janeiro, (30) while in Recife it was detected only after 1996, within PNCD larval surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti, (28) although Culex quinquefasciatus females have been collected naturally infected with ZIKV. (29) Besides that, the presence of Ae. albopictus in Brazil was first recorded in 1986 in Rio de Janeiro, (30) while in Recife it was detected only after 1996, within PNCD larval surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti cooccurs with other domestic and peridomestic mosquitoes such as Culex quinquefasciatus and Aedes albopictus that frequently bite humans. Natural ZIKV infections have been reported in these species, and thus, they came under suspicion as alternative vectors [ 24 , 25 , 26 , 27 ]. Concerning Ae.…”
Section: Introductionmentioning
confidence: 99%
“…In another 16 studies, ZIKV infection was confirmed but without infected salivary glands or transmission (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). In a study conducted in Kédougou, Senegal (30), the ZIKV was identified in a single female Culex perfuscus (Edwards) mosquito.…”
Section: Study Selectionmentioning
confidence: 98%